Prognostic value of Amyloid PET in Real-World Amnestic MCI: Influence of reader experience and interpretation method - Beatriz Echeveste; Edgar Fernando Guillén; Elena Prieto; Katharina C. E. Hirschmüller; Mario Riverol; Javier Arbizu (European Journal of Nuclear Medicine and Molecular Imaging, 2026)
Abstract Purpose This study assessed the prognostic value and inter-/intra-observer reliability of three amyloid PET interpretation methods—conventional visual reading, assisted visual interpretation and standardized uptake value ratio (SUVR)-based quantification—for predicting conversion to Alzheimer’s disease (AD). Methods This retrospective longitudinal study included 145 patients with amnestic mild cognitive impairment who underwent amyloid PET and were followed for up to 8 years at a single memory clinic. Two certified nuclear medicine physicians performed structured visual reads and assisted visual interpretations. Semiquantitative SUVR thresholds validated in prior studies were applied as a third method. Inter- and intra-observer agreement was assessed using Cohen’s kappa (κ). Cox regression models estimated the association of conversion to AD in PET-positive versus PET-negative patients for each method, adjusting for age, sex and education. Results Inter-observer agreement was excellent for structured visual reading (κ = 0.877) and assisted visual interpretation (κ = 0.904). Intra-observer reliability was also high (κ = 0.891 for Reader 1; κ = 0.859 for Reader 2). Consensus agreement for the assisted method reached κ = 0.936. Amyloid PET positivity was strongly associated with progression to AD across all methods. Hazard ratios were highest for assisted visual interpretation (HR = 3.23, 95% CI 1.94–5.38, p < 0.0001), followed by SUVR quantification (HR = 2.19, 95% CI 1.55–3.10, p < 0.0001) and structured visual reading (HR = 1.83, 95% CI 1.10–3.06, p = 0.02). Conclusion Amyloid PET positivity consistently predicted conversion to AD regardless of interpretation method. Assisted visual and semiquantitative approaches showed numerically higher prognostic discrimination, while expert structured visual reading remained clinically reliable.